(untitled) (Plant Tissue Culture and Biotechnology, 2020)
Artemisia annua L. axenic plants were used to induce callogeneisis for production of phenolics and plant regeneration. Up to 95% callogenesis from leaf and stem explants on MS supplemented with 2.0 mg/l NAA or 2,4-D + 0.2 mg/l BAP (MSC1 and MSC2) was observed. Lower callus frequency but with improved embryogenic potential was observed upon subculture on medium with reduced auxin and increased BAP concentration (0.5 mg/l NAA or 2,4-D + 0.5 mg/l BAP) (MSC3 and MSC4). The leafinduced callus on NAA/BAP (MSC3) showed best antioxidant potential. Induced shoot regeneration occurred upon high concentration BAP combined with NAA rather than with 2,4-D (0.25 mg/l NAA or 2,4-D + 1.0 mg/l BAP, MSR 1 and MSR2, respectively). Optimal shoot multiplication and rooting were obtained on 1.0 mg/l BAP and 0.1 mg/l IBA, respectively, followed by acclimatization of regenerants to greenhouse conditions. This work aims at establishing protocol for A. annua preservation and biosynthesis of natural products. Plant Tissue Cult. & Biotech. 30(1): 97-106, 2020 (June)